The transfer of English legislation to the Scottish context: Lessons from the implementation of the Football Banning Order in Scotland. (July 2013) - Hamilton-Smith, Niall; Hopkins, Matt
This article compares the enactment of Football Banning Order legislation in Scotland to that in England and Wales. Football Banning Orders evolved in England and Wales through the 1990s into a particular form of hybrid legislation, culminating in the Football (Disorder) Act of 2000. The legislation was not introduced into Scotland until the Police, Public Order and Criminal Justice (Scotland) Bill in 2006. By 2010, it appeared that orders were being under-utilized in Scotland. This raised questions as to whether there was less need for orders within the context of Scottish football, whether the legislation was either being poorly implemented or if imposing orders was being actively resisted. In focusing primarily on the utilization of the legislation by police on the ground, this article questions whether the football or policing contexts are markedly different in the two jurisdictions. We argue that one of the dominant explanations for the comparatively low use of orders in Scotland relates not to the content or interpretation of the particular legislation involved, but to broader differences in how criminal justice legislation is typically enacted.